2017
DOI: 10.1016/j.msec.2017.03.119
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline phosphatase binds tenaciously to titanium; implications for biological surface evaluation following bone implant retrieval

Abstract: Enhancing the performance and longevity of titanium (Ti) implants continues to be a significant developmental theme in contemporary biomaterials design. Our specific focus pertains to the surface functionalisation of Ti using the bioactive lipid, lysophosphatidic acid (LPA) and certain phosphatase-resistant analogues of LPA. Coating survivorship to a plethora of testing regimens is required to align with due regulatory process before novel biomaterials can enter clinical trials. One of the key acceptance crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…The findings presented in this report for Sawbone™-implanted Ti6Al4V dental screws are encouraging as anticipated from our previous work [ 42 ]; FHBP-Ti6Al4V dental screws supported a good maturation response of osteoblasts to 1,25D. The extent of cellular maturation was similar to FHBP-Ti6Al4V screws inserted into the cancellous bone substitute.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The findings presented in this report for Sawbone™-implanted Ti6Al4V dental screws are encouraging as anticipated from our previous work [ 42 ]; FHBP-Ti6Al4V dental screws supported a good maturation response of osteoblasts to 1,25D. The extent of cellular maturation was similar to FHBP-Ti6Al4V screws inserted into the cancellous bone substitute.…”
Section: Discussionsupporting
confidence: 87%
“…To this end, we have focussed on FHBP-coating stability to long-term (2 years) ambient storage, survivorship to γ-irradiation and persistence of the Ti6Al4V coating following insertion into a mock bone substitute, Sawbone™. With regard the latter, this approach has been informed by our studies using juvenile porcine mandibles and FHBP-functionalised dental screws [ 42 ]. We quickly learned that the abundant ALP in the bone tissue rapidly adsorbed (within minutes) to implanted Ti6Al4V screws.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in osseointegration observed in the hydrophilic surface implants in DBB and HA/TCP grafted areas was associated with an increased expression of BMP‐2 and ALP proteins in the bone tissue close to the surface of the implants compared with machined surface implants. Since these proteins are related to an increased differentiation and osteoblastic function and to the formation of bone tissue (Cheng et al, ; Fahmy‐Garcia, van Driel, Witte‐Buoma, Walles, & van Farrell, ; Mansell, Shiel, Harwood, & Stephens, ), it can be inferred that the increased expression of these proteins may enable an enhancement of the osseointegration promoted by hydrophilic surfaces. Indeed, in vitro studies with osteoblastic lineage cells demonstrated that hydrophilic implant surfaces enhance the expression of important proteins for bone tissue formation, such as VEGF, ALP, OPG, and TGFβ1 (Rausch‐fan, Qu, Wieland, Matejka, & Schedle, ), improving adhesion, proliferation, differentiation, and activation of osteoblastic activity (Thalji, Gretzer, & Cooper, ; Zhao et al, ).…”
Section: Discussionmentioning
confidence: 99%